Investigation of the effect of medium in the preparation of alendronate: till now the best synthesis in the presence of an ionic liquid additive. Issue 3 (3rd May 2017) - Nagy, Dávid Illés; Grün, Alajos; Garadnay, Sándor; Greiner, István; Keglevich, György
Abstract: The synthesis of the drug alendronate from γ‐aminobutyric acid and phosphorus trichloride/phosphorous acid as the P‐reagents is revisited using methanesulfonic acid and sulfolane as solvents and ionic liquids (ILs) as additives according to a novel approach. Besides elaborating efficient synthetic methods with a record yield of up to 80%, the misleading literature data were also clarified. It is a novel trend to use ILs as only catalysts or additives and not as solvents.